INFORMATION & TECHNOLOGY AUDIT OF E-GOVERNMENT USING COBIT A LITERATURE REVIEW - Zitnaa Dhiaaul Kusnaa Washilatul Arba'ah; Ema Utami; Alva Hendi Muhammad (JIKO (Jurnal Informatika dan Komputer), 2023)
The Indonesian government continues to strive to improve public services to meet global demands, one of which is the development of technology such as a broad and integrated internet known as e-government. In implementing the e-government concept, it is necessary to have an IT audit to align the IT management process with the plans, objectives, and business strategies of government institutions. One framework that can be used as a standard is COBIT. This study uses the Systematic Literature Review research method to answer Research Questions (RQ): RQ1 regarding how the COBIT framework is used in IT audit case studies, especially in the e-government field, RQ2 regarding the COBIT domain used in research. The results of the study obtained 32 journals that were selected through a literature search process, literature selection according to criteria, and quality assessment. The results of the study, especially in the context of the main research question, namely the journals reviewed using the COBIT framework with various versions in evaluating e-government implementation. In COBIT there is a workflow that starts from identifying problems in the organization to analyzing capability level. In this study, it is known that the COBIT 2019 version is more adaptable to organizational conditions and technological developments because this version has more domains and design factors have been added (answer RQ1). The COBIT framework has 5 domains, namely the EDM, APO, BAI, DSS, and MEA domains. The most dominant domains used in assessing e-government implementation in journals are the APO and DSS (answer RQ2).